Accountability in Guidance and Counseling Services in Madrasah: Challenges and Urgency - Angelina, Putri Ria; Nurihsan, Juntika; Suherman, Uman; Yustiana, Yusi Riksa (TA`DIBUNA, 2025)
Management, evaluation, and accountability issues remain problems in guidance and counseling services. This study aims to explore the perceptions of guidance and counseling (BK) teachers in Madrasah Tsanawiyah Bogor regarding accountability in guidance and counseling services. This study uses a descriptive qualitative approach. The research subjects were eight BK teachers at Madrasah Tsanawiyah Bogor who were selected using purposive sampling. Structured interviews were used for data collection. The data were analyzed using thematic analysis. This study found that BK teachers’ perceptions of accountability were divided into five main categories: (1) conceptual understanding of accountability, (2) documentation and reporting practices, (3) barriers to implementing accountability, (4) understanding of MEASURE, and (5) analysis of each aspect of MEASURE. BK teachers understanding of accountability tended to be general, documentation practices were still limited to administrative aspects, and there were various obstacles in the implementation of accountability. The conclusion of this study is BK teachers’ perceptions of accountability are still in the early stages of understanding and basic implementation. Structural interventions such as training, integration of digital documentation systems, and strengthening of regulations are needed to encourage more reflective and collaborative accountability. Keywords: Accountability, Guidance and Counseling Services, Perception, Guidance and Counseling Teachers, Madrasah